Exploring the dynamics of didactic practices in ratio learning: a qualitative study of teachers’ instructional strategies and student engagement in junior secondary mathematics - Azis; Jarnawi Afgani Dahlan (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: The teaching of ratio remains a significant challenge in mathematics education, as students often struggle to understand multiplicative relationships and tend to rely on procedural reasoning rather than conceptual understanding. Previous studies have mainly focused on students’ conceptual difficulties, while limited attention has been given to how teachers’ didactic practices influence students’ engagement and understanding. Aims: This study aims to analyze the dynamics of didactical practices in ratio learning, focusing on instructional strategies, classroom interaction, and student engagement, and offers a novel contribution by examining how didactical practices shape variations in student engagement in real classroom contexts. Method: This research employed a qualitative case study design involving one mathematics teacher and 28 seventh-grade students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using thematic analysis. Results: The findings indicate that teaching practices were dominated by direct instruction combined with contextual examples, which supported initial understanding but limited deeper conceptual exploration. Approximately 60% of students were actively engaged, while the others tended to be passive. Student interaction was mostly procedural, and the use of a reward system increased participation but encouraged performance-oriented behavior. Conclusion: These findings highlight the important role of didactic practices in shaping students’ engagement and understanding of ratio. It is recommended that teachers adopt more student-centered approaches, such as structured discussions and contextual problem-solving, to enhance conceptual understanding and equitable participation in mathematics learning.